Populist Capture of Foreign Policy Institutions: The Orbán Government and the De‐Europeanization of Hungarian Foreign Policy. (11th July 2022) - Müller, Patrick; Gazsi, David
Abstract: Despite a growing interest in the relationship between populism and foreign policy, we know little about how populists in power engage with Europeanized foreign policy institutions. Bridging between research on populism and foreign policy (de‐)Europeanization, this article develops a theoretical framework for examining the impact of PRR parties in government on core features of national foreign policy institutions. First, it identifies three dimensions – organizational priorities, the allocation of authority, and organizational culture – and related indicators for the assessment of foreign policy de‐Europeanization. Second, it argues that the impact of PRR parties in government on national foreign policy institutions depends on two main factors: their 'foreign policy preferences' and their 'action capacity'. Whilst the article demonstrates substantial de‐Europeanization in Hungary's foreign policy institutions under successive Orbán governments, it also shows that the possession of a strong action capacity alone is not enough for institutional changes to take place.